Teacher Knowledge and Readiness for Inclusive Education: Supporting Children with Special Needs - Zurratul Muna; Rini Julistia; Widi Astuti; Dwi Iramadhani; Yara Andita Anastasya; Siti Nur Atikah Bt Ismail Ismail; Syakira Syakira; Lusi Nurmala Sari (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study aims to examine the relationship between regular teachers’ knowledge and their readiness to accept students with special needs. It addresses the challenges of limited teacher knowledge and insufficient readiness in inclusive classrooms, arguing that comprehensive teacher knowledge is a critical determinant of the successful implementation of high-quality inclusive education. Design/methods/approach – The study employed a quantitative approach with an associative research design. Participants were 208 early years teachers in public school selected through cluster sampling across four subdistricts of Lhokseumawe. Data were collected using a questionnaire that assessed four dimensions of knowledge, factual, conceptual, procedural, and metacognitive, and three aspects of readiness: physical, mental, and emotional readiness; motivation and goal orientation; and skills and knowledge readiness. Data were analyzed using Spearman’s rank correlation and multiple linear regression in SPSS. Findings – The findings supported the proposed hypothesis, revealing a strong and positive relationship between teachers’ knowledge and their readiness to accept students with special needs (ρ = 0.673, p < .01). The regression analysis further indicated that metacognitive knowledge was the strongest predictor of teacher readiness (β = 0.399), followed by procedural knowledge (β = 0.294) and factual knowledge (β = 0.176). Research implications/limitations – The study is limited by its focus on public schools in the early childhood age range, which may restrict the generalizability of the findings to other educational contexts. Practical implications – Nevertheless, the results highlight the importance of strengthening teachers’ knowledge, particularly metacognitive and procedural knowledge, as a strategic means of enhancing readiness for inclusive education. Originality/value – The study offers practical value for policymakers, school administrators, and teacher education institutions by identifying specific knowledge domains that should be prioritized in professional development programs. Strengthening metacognitive and procedural knowledge may enhance teachers’ readiness and contribute to the successful implementation of inclusive education policies.